Descent among the Wayú. Concepts and social meanings - Alessandro Mancuso (Journal de la Société des Américanistes)
Descent among the Wayú. Concepts and social meanings. Taking the contemporary rethinking of the descent notion in Lowland South American ethnography as a starting point, the article provides an analysis of matrilineal descent among the Wayú. Using new ethnographical data, special attention is paid to indigenous concepts and to the way matrilineal descent articulates with other principles of social classification. By virtue of the role that matrilineal descent plays in defining territoriality and in feuds, the Wayú offer a very interesting case for rethinking the theoretical and comparative debate about the indigenous societies of Lowland South America and for reflecting on the complexity of the interactions between structure and history in this area.